Character Education Implementation Through Tahfidzul Qur’an Teaching in SMPIT Ar-Rayyan Surabaya - As rori (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
Abstract : Criminal case done by Indonesian children has increased that showed how important character education. In building character values, a school is needed to have an activity program. SMPIT Ar Rayyan has Tahfidzul Qur’an program in character education. This study aimed to discuss how character education is implemented through teaching in SMPIT Ar Rayyan Surabaya, and how Tahfidzul Qur’an teaching has done in SMPIT Ar Rayyan Surabaya, and what character values are growths through Tahfidzul Qur’an teaching in SMPIT Ar Rayyan Surabaya.  The method used in this study was descriptive qualitative. In this study, data collection technique used three methods i.e. interview, observation, and documentation. According to study result in SMPIT Ar Rayyan Surabaya, it was found that character education has been well enough implemented in teaching Tahfidzul Qur’an, viz. it was from teaching stages, the teaching method, and the teaching evaluation. Tahfidzul Qur’an teaching implemented in SMPIT Ar-Rayyan used tasmi’ and mura ja’ah methods. The character values growth were religious, discipline, hard work, independent, friendly, love to read, and responsible. Keywords:     Character Education Implementation, Tahfidz